Educação ambiental corporativa em meio eletrônico - Bechert, Carina Bárbara Ribas de Oliveira (2009)
The environment concerning is a topic that has being discussed today in all social spheres. The man, as an important integral and transformative agent in society, absorbs and uses different learning vehicles, among them beingthe technology. The development of new educational technologies provides a relevant access to the knowledge and offers tools to the requirement of continuing education, especially in corporate environments. These alternatives reveal their importance in providing the cost saving in training process, the reduction in using natural resources, as well as due to be able to promote a quick access to the individuals. The herein study aimed to evaluate the use of electronic tools (communication networks) to Corporate Environmental Education (EE), using a case study in three target audiences, for the theme “The Pollution by Medicines”, two of them that had already dealt with educational campaigns of medicines collection. Aiming the diagnosis of environmental perceptions of the actors, a previous-test (questionnaire) was assigned in order to get the socio-economic profile of the target audiences, and also to evaluate their affinity to the use of electronic tools, and to determine the extent of prior environmental knowledge. The data showed the lack of knowledge about the herein environmental issue. Based on these results, two proposals of socioenvironmental education were created, one of them using a journalistic approach, called CHED proposal, and the other one based on learning from comics approach, called LUGRA. The participation of actors in the proposals were evaluated based on the methodology of the Collective’s Discourse (CD), showing the actors’perception and how the knowledge acquiring process was carried out. The results showed a median adherence of individuals to comply with the step of sending responses, better performance on the environmental responses from the actors that had already dealt with the proposed environmental issue. The results showed the potential of applying electronic network communication systems to the Corporate Environmental Education of multipliers of environmental concepts.